The extent of voluntary corporate disclosure in the Egyptian Stock Exchange: Its determinants and consequences. Issue 2 (2nd May 2017) - Kamel, Hany; Awadallah, Emad
Abstract : Purpose: The purpose of this paper is to investigate the current level of voluntary corporate disclosure in the Egyptian Stock Exchange. In addition, it explores the factors influencing the extensiveness of voluntary disclosure and examines the potential consequences of such disclosure in regards to the phenomenon of earnings management. Design/methodology/approach: A relevant disclosure index to the Egyptian context was adopted to assess the level of voluntary disclosure in the 2010 annual reports of the most actively traded companies listed on the Egyptian Stock Exchange. The relationship between the extent of voluntary disclosure and each specific-related factor was examined using unranked and ranked OLS regression models. Meanwhile, a system of simultaneous equations was performed using a two-stage least squares regression model in order to investigate whether companies with higher levels of voluntary disclosure exhibit lower levels of earnings management practices. Findings: The results indicate that the level of voluntary disclosure is positively responsive to specific corporate attributes, namely, the type of auditing firm and the two industries of Healthcare and Pharmaceuticals, and Chemicals. However, no significant indications were found that firm size, leverage, profitability and liquidity are important determinants of corporate disclosure. Also, the results show no evidence to support the prior anticipation that a higher level of voluntary disclosure reduces the ability of managers to make use of earnings management. On the contrary, it was found that leverage and the tendency of firms to avoid reporting declines in earnings are the main drivers of the phenomenon of earnings management in Egypt. Practical implications: This paper has important implications for both domestic and overseas investors in Egypt as well as the regulatory authorities in the developing economies. Originality/value: The main contribution of this paper is its focus on the extent of voluntary disclosure in a developing country such as Egypt, which has a high potential for economic growth in the near future. Besides, this paper is the first to examine the relationship between the level of voluntary disclosure and the phenomenon of earnings management in the Egyptian context.